Stratégies scripturales dans la pratique intertextuelle d’Amine Zaoui - BOUGHACHICHE, Meriem (Journal of Human Sciences, 2018)
In the continuation of generations of French-speaking Moroccan writers, there seems to be an extension with many writings including the double temptation between revolution and "work." This is fully illustrated by objective sharing as an extension of the star of Kateb Yassine and Rashid Boujdra, where language is used as a means of expressing absolute freedom about " In patriarchal patriarchal society, the extreme is alienated from traditional forms These strategies and writing techniques are found in the novel and work of Amine Zaoui. We will see that ambiguity and plurality are directly inspired by the work of writer Yassin and Rashid Boujdra. In addition, the work feeds on the Arab-Muslim culture. Amine Zaoui begins his poetic style of delusions and hallucinations with mixing Truth and fiction with a lot of techniques that also generate modernity and ridicule expressing hints through stories of love, incest, blood, death, desire and faith .